Physics of runaway electrons with shattered pellet injection at JET. (2nd February 2022) - Reux, C; Paz-Soldan, C; Eidietis, N; Lehnen, M; Aleynikov, P; Silburn, S; Bandaru, V; Ficker, O; Hoelzl, M; Hollmann, E M; Jachmich, S; Joffrin, E; et al.
Abstract: Runaway electrons (REs) created during tokamak disruptions pose a threat to the reliable operation of future larger machines. Experiments using shattered pellet injection (SPI) have been carried out at the JET tokamak to investigate ways to prevent their generation or suppress them if avoidance is not sufficient. Avoidance is possible if the SPI contains a sufficiently low fraction of high-Z material, or if it is fired early in advance of a disruption prone to runaway generation. These results are consistent with previous similar findings obtained with Massive Gas Injection. Suppression of an already accelerated beam is not efficient using High-Z material, but deuterium leads to harmless terminations without heat loads. This effect is due to the combination of a large magnetohydrodynamic instability scattering REs on a large area and the absence of runaway regeneration during the subsequent current collapse thanks to the flushing of high-Z impurities from the runaway companion plasma. This effect also works in situations where the runaway beam moves upwards and undergoes scraping-off on the wall.